THE IMPACT OF CONSUMPTION VALUES ON HOUSEHOLD’S BUYING BEHAVIOUR TOWARDS GREEN GROCERY PRODUCTS - Mei Ling Goh; Seng Huat Tan; Sook Fern Yeo; Pui Yen Tan (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study aims to examine the impact of consumption values on household’s buying behaviour towards green grocery products. Concern for healthy lifestyles among households has created a high demand for environmental-friendly or natural products. This has shown that the green products market has the perspective to grow. In order to have an effective marketing strategy, there is a need for marketers to understand the buying behaviour of households towards green grocery products. The theory of consumption values was used to explain the household’s buying behaviour towards green grocery products. Five variables from the theory, namely functional value, emotional value, social value, epistemic value, and conditional value were included in the research model to explain household buying behaviour towards green grocery products. A total of 200 households were recruited using a convenience sampling approach. Data were collected with a set of self-administered questionnaires. The variables were validated and tested using Structural Equation modelling (PLS-SEM). The findings have shown that both conditional value and functional value positively influence household’s buying behaviour towards green grocery products with the exception of emotional value, social value, and epistemic value. This study has thus indicated that elements such as quality, price, and promotion of the green grocery products are important in the marketing strategies planning in attracting more consumers. This study has also provided an insight into the household’s buying behaviour towards green grocery products in Malaysian context.